Odorant receptor heterodimerization in the olfactory system of Drosophila melanogaster. - Neuhaus, E.M.; Gisselmann, G.; Zhang, W.; Dooley, R.; Störtkuhl, K.; Hatt, H. (Nature Neuroscience, 2005)
Despite increasing knowledge about dimerization of G-protein-coupled receptors, nothing is known about dimerization in the largest subfamily, odorant receptors. Using a combination of biochemical and electrophysiological approaches, we demonstrate here that odorant receptors can dimerize. DOR83b, an odorant receptor that is ubiquitously expressed in olfactory neurons from Drosophila melanogaster and highly conserved among insect species, forms heterodimeric complexes with other odorant-receptor proteins, which strongly increases their functionality.